PEMENUHAN KEBUTUHAN DASAR IBU HAMIL BERHUBUNGAN DENGAN KELUHAN NYERI PUNGGUNG PADA PEKERJA KERAJINAN ANYAMAN - Ni Putu Aryani; Baiq Ricca Afrida; Susilia Idyawati; Nurul Hikmah Annisa; Meda Yuliani (Jurnal Doppler, 2022)
Pregnancy is part of the cycle of a woman's cycle where the process of pregnancy will cause a woman to experience several changes in herself. These changes include physical, mental and social. Basic Needs Pregnant women physically need to be met so that the mother in her pregnancy is maintained healthy. The purpose of this study was to determine the relationship between the fulfillment of the basic needs of pregnant women with complaints of back pain in weaving crafts workers. This research is an analytic observational study. The research location is West Lombok. The time of the study was from July-August 2022. In this study, the population was 40 pregnant women. The sample taken is using a total sample technique of 40 people. Data processing in this study followed the steps, including editing, coding, entry, tabulating and cleaning. Analysis of the data used is using the Chi-Square test. The results of the study found that most of the respondents were aged 20-35 years as many as 22 people (55.0%), with elementary education as many as 16 people (40.0%). While the fulfillment of basic human needs in pregnant women is mostly not met in oxygenation (62.5%), nutrition (60.0%), personal hygiene (57.5%), elimination (55.0%), clothing (60, 0%), sexual (52.5%), mobilization/body mechanics (55.0%), resting (62.5%) and most of them complained of back pain (55.5%). There is no relationship between the fulfillment of oxygenation and nutrition needs with back pain complaints. There is a relationship between personal hygiene, elimination, clothing, sex, mobilization and sleep rest. Keywords: basic needs, back pain, pregnant women